2015
DOI: 10.1016/j.jconrel.2015.10.035
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of vincristine and doxorubicin binding and release from silk films

Abstract: Sustained release drug delivery systems remain a major clinical need for small molecule therapeutics in oncology. Here, mechanisms of small molecule interactions with silk protein films were studied with cationic oncology drugs, vincristine and doxorubicin, with a focus on hydrophobicity (non-ionic surfactant) and charge (pH and ionic strength). Interactions were primarily driven by charge interactions between the positively charged drugs and the negatively charged groups within the silk films. Exploiting chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
82
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 61 publications
(85 citation statements)
references
References 48 publications
(75 reference statements)
2
82
0
Order By: Relevance
“…32-37 As drug carriers, silk particles, films and hydrogels show capability to stabilize the drugs and control drug release through adjusting endogenous parameters such as the crystallinity. [38][39][40][41][42] Recently, DOX-loaded silk drug-release systems with pH-responsive properties were developed and used for the treatment of cancers, suggesting feasibility of silk-based injectable hydrogels for localized chemotherapy. 2,43,44 However, similar to the injectable hydrogels reported previously, the precise control of gelation kinetics for these silk hydrogels remains a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…32-37 As drug carriers, silk particles, films and hydrogels show capability to stabilize the drugs and control drug release through adjusting endogenous parameters such as the crystallinity. [38][39][40][41][42] Recently, DOX-loaded silk drug-release systems with pH-responsive properties were developed and used for the treatment of cancers, suggesting feasibility of silk-based injectable hydrogels for localized chemotherapy. 2,43,44 However, similar to the injectable hydrogels reported previously, the precise control of gelation kinetics for these silk hydrogels remains a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, Coburn et al[8], has shown that vincristine binds to silk fibroin films via electrostatic interactions, allowing for controlled release over three weeks. The foam-base system used in this work employs this same principle for vincristine binding and release.…”
Section: Discussionmentioning
confidence: 99%
“…One milliliter of the vincristine solution was added to silk fibroin foams in sterile, 1.5 mL Eppendorf tubes. The vincristine was allowed to adsorb to the silk fibroin foams as previously reported [6, 8]. …”
Section: Methodsmentioning
confidence: 99%
“…Under aseptic conditions, silk foams were immersed in an aqueous solution of 400 μg/mL doxorubicin hydrochloride. Doxorubicin was allowed to bind to the silk foam for one week [20, 21]. …”
Section: Methodsmentioning
confidence: 99%